Survival After the Diagnosis of Mild‐to‐Moderate Alzheimer's Disease Dementia: A 15‐Year National Cohort Study in Taiwan - Sun, Yu; Liu, Chih‐Ching; Li, Chung‐Yi; Chiu, Ming‐Jang (International journal of geriatric psychiatry, 2024)
ABSTRACT Objectives Pharmacological and non‐pharmacological interventions are mostly designed for patients with early Alzheimer's disease (AD) dementia. Long‐term case management and planning for the remainder of life with disability require an estimation of the survival duration. Methods This cohort study utilized data from the National Health Insurance Research Database, Taiwan, to identify incident cases of mild‐to‐moderate AD dementia diagnosed from 2000 to 2002, followed through December 31, 2017. A multivariate Cox proportional hazards regression model was constructed to compare the independent effects of age, sex, and comorbidities on all‐cause mortality risk. Cumulative survival rates and survival times were estimated. Results A total of 5258 incident cases were identified, all treated with cholinesterase inhibitors after diagnosis confirmation by an expert committee. During the 15‐year follow‐up period, 4331 deaths occurred. The 1‐, 3‐, 5‐, 10‐, and 15‐year cumulative survival rates were 95, 92, 67, 37, and 18, respectively. The median (95% CI) survival time after diagnosis was 7.69 (7.46–7.90) years overall, 6.37 (6.06–6.65) years in men, and 8.81 (8.49–9.12) years in women. After stratification by age and number of comorbidities, the median survival time ranged from 13.72 (ages 40–64) to 5.29 (ages ≥ 80) years among those without comorbidities. For those with ≥ 3 comorbidities, the median survival times decreased to 6.43 for individuals diagnosed at ages 40–64 and to 2.98 years for those diagnosed at age 80 or older. Conclusions This nationwide, large, long‐term cohort study provided survival rates and durations from diagnosis to death, varying by sex, age group, and presence/number of comorbidities. This information can serve as a foundation for further cost‐effectiveness studies on new treatments, and may aid clinicians, patients, and families in shared decision‐making and advance personalized care planning for early dementia cases.